Governance, Government, and the Search for New Provider Models - Richard B. Saltman; Antonio Duran (Kerman University of Medical Sciences, 2016)
A central problem in designing effective models of provider governance in health systems has been to ensure an appropriate balance between the concerns of public sector and/or government decision-makers, on the one hand, and of non-governmental health services actors in civil society and private life, on the other. In tax-funded European health systems up to the 1980s, the state and other public sector decision-makers played a dominant role over health service provision, typically operating hospitals through national or regional governments on a command-and-control basis. In a number of countries, however, this state role has started to change, with governments first stepping out of direct service provision and now de facto pushed to focus more on steering provider organizations rather than on direct public management. In this new approach to provider governance, the state has pulled back into a regulatory role that introduces market-like incentives and management structures, which then apply to both public and private sector providers alike. This article examines some of the main operational complexities in implementing this new governance reality/strategy, specifically from a service provision (as opposed to mostly a financing or even regulatory) perspective. After briefly reviewing some of the key theoretical dilemmas, the paper presents two case studies where this new approach was put into practice: primary care in Sweden and hospitals in Spain. The article concludes that good governance today needs to reflect practical operational realities if it is to have the desired effect on health sector reform outcome.